Metformin Exposure and Risk of Hypertensive Disorders of Pregnancy in Patients with Type 2 Diabetes - Racine, Jenna L.; Adams, Jacquelyn H.; Antony, Kathleen M.; Hoppe, Kara K.; Iruretagoyena, Jesus I.; Stewart, Katharina S.; Eddy, April; Rhoades, Janine S. (American Journal of Perinatology, 2021)
Objective Metformin has been found to have a role in promoting vascular remodeling and angiogenesis which may reduce the risk of developing preeclampsia. Prior studies have shown a decrease in the incidence of hypertensive disorders of pregnancy in patients with type 2 and gestational diabetes taking metformin. We hypothesize metformin exposure decreases the risk of developing hypertension in patients with type 2 diabetes.Study Design Retrospective cohort study from 2009 to 2019 of singleton pregnancies was complicated by type 2 diabetes. We compared patients who received metformin throughout pregnancy to those with no metformin exposure. The primary outcome was a hypertension composite defined as gestational hypertension, preeclampsia with or without severe features, HELLP syndrome, or eclampsia. Individual hypertensive outcomes and neonatal outcomes were secondarily evaluated. Logistic regression was used to adjust for confounding variables.Results A total of 254 pregnancies were included. Women exposed to metformin were significantly less likely to develop hypertension composite compared with nonexposed women (22.7 vs. 33.1%, aOR 0.53, 95% CI 0.29–0.96). The incidence of preeclampsia with severe features was also significantly lower in those who received metformin compared with those who did not (12.1 vs. 20.7%, aOR 0.38, 95% CI 0.18–0.81). There were no differences in preterm birth prior to 34 or 37 weeks, fetal growth restriction, or birth weight between the study groups. A subgroup analysis of women without chronic hypertension also had a significantly lower risk of developing preeclampsia with severe features (7.6 vs. 17.8%, aOR 0.35, 95% CI 0.13–0.94).Conclusion Metformin exposure was associated with a decreased risk of composite hypertensive disorders of pregnancy in patients with pregestational type 2 diabetes. These data suggest that there may be benefit to metformin administration beyond glycemic control in this patient population.Key Points
Keywords: type 2 diabetes; metformin; hypertension; preeclampsia